IMPROVING THE STUDENTS’ LISTENING SKILL BY USING BRITISH BROADCASTING CORPORATION (BBC) LEARNING ENGLISH MEDIA IN ENGLISH LEARNING - Nurislami, Rb. Amalia; Sangkala, Ismail; Sastrawati, Ika (FKIP Unismuh Makassar, 2024)
The aimed of this research was to find out does BBC English Learning improve the students’ listening skill and How is the students’ interest toward BBC media Learning English to improve students’ listening skill. The research design of this research was Classroom Action Research. It was conducted in 2 cycles. The research used a test and a questionnaire as instruments to collect the data. The subjects in this research were the students of XII MIPA 4 class of SMAN 4 Makassar. The results of this research there was a significant improvement of students’ listening skills. It can be shown in the mean of students’ score of the D-test in cycle I and test in cycle II. The mean of the test in cycle I (84,19) is higher than in D-test (75,48) Then, the mean test of cycle II (93,55) is higher than in cycle I (84,19). The score improvement of a cycle I to cycle II (9,36) or 9%. The results showed that there was a significant improvement of students’ listening skill by BBC Learning English media and there were students interest in using (BBC) Learning English media.